Acute toxicity in comprehensive head and neck radiation for nasopharynx and paranasal sinus cancers: cohort comparison of 3D conformal proton therapy and intensity modulated radiation therapy. Issue 1 (December 2016) - McDonald, Mark; Liu, Yuan; Moore, Michael; Johnstone, Peter
Abstract Background To evaluate acute toxicity endpoints in a cohort of patients receiving head and neck radiation with proton therapy or intensity modulated radiation therapy (IMRT). Methods Forty patients received comprehensive head and neck radiation including bilateral cervical nodal radiation, given with or without chemotherapy, for tumors of the nasopharynx, nasal cavity or paranasal sinuses, any T stage, N0-2. Fourteen received comprehensive treatment with proton therapy, and 26 were treated with IMRT, either comprehensively or matched to proton therapy delivered to the primary tumor site. Toxicity endpoints assessed included g-tube dependence at the completion of radiation and at 3 months after radiation, opioid pain medication requirement compared to pretreatment normalized as equivalent morphine dose (EMD) at completion of treatment, and at 1 and 3 months after radiation. Results In a multivariable model including confounding variables of concurrent chemotherapy and involved nodal disease, comprehensive head and neck radiation therapy using proton therapy was associated with a lower opioid pain requirement at the completion of radiation and a lower rate of gastrostomy tube dependence by the completion of radiation therapy and at 3 months after radiation compared to IMRT. Proton therapy was associated with statistically significant lower mean doses to the oral cavity, esophagus, larynx, and parotid glands. In subgroup analysis of 32 patients receiving concurrent chemotherapy, there was a statistically significant correlation with a greater opioid pain medication requirement at the completion of radiation and both increasing mean dose to the oral cavity and to the esophagus. Conclusions Proton therapy was associated with significantly reduced radiation dose to assessed non-target normal tissues and a reduced rate of gastrostomy tube dependence and opioid pain medication requirements. This warrants further evaluation in larger studies, ideally with patient-reported toxicity outcomes and quality of life endpoints.